Towards personalised predictive psychiatry in clinical practice: an ethical perspective. (April 2022) - Lane, Natalie; Broome, Matthew
Summary: Personalised prediction models promise to enhance the speed, accuracy and objectivity of clinical decision-making in psychiatry in the near future. This editorial elucidates key ethical issues at stake in the real-world implementation of prediction models and sets out practical recommendations to begin to address these.